Wewenang Dosen Pembimbing Akademik dalam Mencegah Pelanggaran Akademik Mahasiswa Perspektif Siyāsah Tanfīdziyah - Tegar Setiawan (Jurnal Hukum Lex Generalis, 2026)
This research is motivated by the gap between the normative provisions in the 2019 Academic Guidelines for the Undergraduate Program at Raden Intan State Islamic University of Lampung and their practical implementation regarding the authority of academic supervisors in preventing academic misconduct. Previous research generally positions academic misconduct as individual deviation and has not examined the failure of authority governance and its integration with the Siyāsah Tanfīdziyah perspective. This study is a field research with a purposive sampling technique through interviews. The results show that academic misconduct is not only administrative in nature, but also includes violations of academic integrity such as jockeying and scientific dishonesty. Legally, norms have regulated the authority of academic supervisors, but their implementation has not been effective due to weak mechanisms of evidence, supervision and the absence of standard operating procedures (SOPs). From the Siyāsah Tanfīdziyah perspective, this condition reflects the suboptimal principles of al-amānah and al-‘adl in institutional governance. The novelty of this research lies in the shift in perspective that positions academic misconduct as a failure of authority governance, not merely individual deviation.